2023
DOI: 10.1111/psyg.13028
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between eating problems and the risk of dementia: A retrospective study

Weiyi Sun,
Teruyuki Matsuoka,
Ayu Imai
et al.

Abstract: BackgroundOlder adults and individuals with decreased cognition often experience appetite changes and weight loss. As weight loss can result in cognitive decline, change in appetite may be an important contributor to the onset of dementia. However, there is a lack of relevant studies on this topic. This study aimed to determine the relationship between appetite changes, weight loss, and dementia onset.MethodsA total of 135 patients with normal cognitive function, subjective cognitive impairment, and mild cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Dear Editor, We read with great interest the retrospective study presented by Sun et al 1 which revealed that the elderly who experience weight loss can increase the risk of developing dementia. The outcome may be reasonable from physiological, medical, and psycho-social perspectives.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Dear Editor, We read with great interest the retrospective study presented by Sun et al 1 which revealed that the elderly who experience weight loss can increase the risk of developing dementia. The outcome may be reasonable from physiological, medical, and psycho-social perspectives.…”
mentioning
confidence: 99%
“…4 The possible mechanisms of active caloric restriction benefiting cognition are explained by decreased peripheral insulin concentration, which involves glutamate and γ-aminobutyric acid (GABA)-mediated synaptic plasticity, inducing N-methyl-D-aspartic acid (NMDA) receptor phosphorylation, increasing channel activities of NMDA receptors, and promoting gene expressions to enhance cognition. 1,5 Another Figure 1 The current trend in the publication of research on the relationship between caloric restriction and cognition. potential pathway is neurotrophic factors (such as brain-derived neurotrophic factor), which could help adaptive cellular stress response pathways and protect mature neurons from degeneration.…”
mentioning
confidence: 99%
See 1 more Smart Citation